Betekenislagen van het kerkgebouw: een benadering vanuit de recente tensieve semiotiek - Lukken, Gerard (Jaarboek voor liturgieonderzoek, 2008)
Church buildings can be observed in a multiform manner. This article aims at the description of its intrinsic layers of meaning with the help of recent French tensive semiotics which is an important supplement to classic structural semiotics. First an introduction of some technical semiotic terms is given; then follows a short exploration of the negative meaning layer of the church building as a touristic space, and next its museal dimension is explored. The basic-sacral dimension of the church building and its various gradations in the different periods is examined exhaustively. Subsequently the religious Christian dimension and its relation with the basic-sacral dimension is discussed. Finally the article draws attention to the ritual-liturgical dimension, to the dimension of metonymic relation with the past and to the diaconal dimension.